2009
DOI: 10.3855/jidc.40
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus recovery from cotton towels

Abstract: Background: Staphylococcus aureus is an emerging pathogen afflicting healthy individuals without known risk factors, and methicillinresistant Staphylococcus aureus has been shown to colonize multiple family members sharing households. Because household items such as towels are often shared by family members, this study investigated whether cotton towel absorbency or washing conditions affect Staphylococcus aureus cell viability or cell retention, and whether the levels may be sufficient for person-to-person tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 13 publications
1
13
0
Order By: Relevance
“…The borderline significant negative association of contact with cats on MRSA carriage could not be verified in literature: companion animals and their owners seem to exchange MRSA rather than protecting each other , with cats in lower amounts than with dogs . The borderline risk factor of washing hands can be explained by the fact that MRSA is able to survive for days on water taps, towels and soap . Reversed causality might have been another possibility; farmers might have washed their hands more often when working in a stable with much dust.…”
Section: Discussionmentioning
confidence: 92%
“…The borderline significant negative association of contact with cats on MRSA carriage could not be verified in literature: companion animals and their owners seem to exchange MRSA rather than protecting each other , with cats in lower amounts than with dogs . The borderline risk factor of washing hands can be explained by the fact that MRSA is able to survive for days on water taps, towels and soap . Reversed causality might have been another possibility; farmers might have washed their hands more often when working in a stable with much dust.…”
Section: Discussionmentioning
confidence: 92%
“…Survival (log (10) ) of micro-organisms at different detergency treatment conditions study show, a biological detergent (does not contain bleach) used in a 40°C wash, resulted in the textiles still having contamination from a high initial inoculum ( Table 2). The ability of micro-organisms to survive on textile surfaces is not disputed, however, limited evidence exists surrounding the survival of micro-organisms in household detergents and postdomestic laundering of nurses' uniforms and how this impacts on cross-contamination of healthcare-associated infections (Neeley and Maley 2000;Oller and Mitchell 2009;Mcgovern et al 2010& Woodland et al 2010. In a study conducted by Oller and Mitchell (2009), Egyptian cotton towels inoculated with S. aureus (10 8 ) postwash in water and a water and detergent solution resulted in a survival of between 2 log (10) and 3 log (10) , after 48 h, cells were still viable.…”
Section: Micro-organisms In Detergent Solutionsmentioning
confidence: 99%
“…The ability of micro-organisms to survive on textile surfaces is not disputed, however, limited evidence exists surrounding the survival of micro-organisms in household detergents and postdomestic laundering of nurses' uniforms and how this impacts on cross-contamination of healthcare-associated infections (Neeley and Maley 2000;Oller and Mitchell 2009;Mcgovern et al 2010& Woodland et al 2010. In a study conducted by Oller and Mitchell (2009), Egyptian cotton towels inoculated with S. aureus (10 8 ) postwash in water and a water and detergent solution resulted in a survival of between 2 log (10) and 3 log (10) , after 48 h, cells were still viable. Neeley and Maley (2000) also found that S. aureus survived on cotton for 16-21 days and on polyester for up to 56 days.…”
Section: Micro-organisms In Detergent Solutionsmentioning
confidence: 99%
“…5,6,1113 A case-control study in Manhattan found that household environments of patients with recent MRSA infections were more likely to be contaminated with MRSA compared to control households. 9 Additionally, transmission of MRSA between pets and humans has been proposed, but the directionality is unclear.…”
Section: Introductionmentioning
confidence: 99%